DEVELOPMENT OF SPEED ENDURANCE AND COORDINATION ABILITIES OF SCHOOLCHILDREN WITH THE HELP OF EXERCISE CLASSICS - Polevoy, Georgiy (Revista Tempos e Espaços em Educação, 2019)
The aim of the study is to study the influence of the exercise «Classic’s» in the lessons of physical culture in school on the performance of speed endurance and coordination abilities of children 8-9 years. Material – the Study was conducted during the school year in a regular school in Kirov, Russia. The study involved schoolchildren from the second grade in the amount of 50 people. The lesson on physical culture at school lasted for 40 minutes, during the week there were two lessons. Indicators of speed endurance were determined by the test «Jumping through rope», indicators of coordination abilities were determined by the test «Shuttle run». Mathematical processing of the results of the study was carried out using programs Excel-2016, Bio-Stat-2009, T-Student, reliability at P<0.05. Results – after nine months of pedagogical experiment the results improved in both groups. The children in the control group improved their performance in the «Jumping through rope» test by 13.1% (P<0.05), and the performance in the «Shuttle run» test improved from 10.1±0.9 seconds to 9.7±0.5 seconds (P<0.05). The schoolchildren from the EG had significantly improved in both tests. In the test «Jumping through rope», the result has improved by 40% (P<0.05), and in the test «Shuttle run» the result has improved from 10.5±0.8 to 8.5 h±0.5 h (P<0.05). The results of the study in the EG say about the effectiveness of the use of exercises «Classic’s» in physical education lessons at school. Conclusion – if at each lesson on physical culture at school schoolchildren will perform the exercise «Classic’s» the level of development of speed endurance and coordination abilities will increase significantly.